1999
DOI: 10.1115/1.483237
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of the Bubbly Flow Beneath Partial Attached Cavities Using Electrical Impedance Probes

Abstract: Surface electrical impedance probes are used to examine the bubbly flow beneath and in the closure region of partial attached cavities. A series of electrodes were mounted flush to the surface of a cavitating hydrofoil to detect the presence of liquid or vapor through changes in the impedance of the local fluid medium. Signals from the electrical probes were used to determine the near-surface gas-phase velocity and the shedding frequency of the gas phase. The impedance technique is shown to have the potential … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
7
2
1

Relationship

4
6

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 7 publications
0
13
0
Order By: Relevance
“…Subsequent studies have demonstrated that inception involves intermittent and short-lived attachment of travelling bubble cavitation to the surface near the minimum pressure point (Blake, Wolpert & Geib 1977; Ceccio & Brennen 1991; De Chizelle, Ceccio & Brennen 1995; Li & Ceccio 1996; Laberteaux et al. 1998; George, Iyer & Ceccio 2000). The important role of boundary layers was discussed first by Arakeri & Acosta (1973).…”
Section: Introductionmentioning
confidence: 99%
“…Subsequent studies have demonstrated that inception involves intermittent and short-lived attachment of travelling bubble cavitation to the surface near the minimum pressure point (Blake, Wolpert & Geib 1977; Ceccio & Brennen 1991; De Chizelle, Ceccio & Brennen 1995; Li & Ceccio 1996; Laberteaux et al. 1998; George, Iyer & Ceccio 2000). The important role of boundary layers was discussed first by Arakeri & Acosta (1973).…”
Section: Introductionmentioning
confidence: 99%
“…Kawanami et al (2002) used laser holography to study the structure of a cloud shed from a hydrofoil and estimated the bubble size distribution. Measurements of the re-entrant flow underneath the cavity using electrical impedance probes was done by Pham, Larrarte & Fruman (1999) and George, Iyer & Ceccio (2000). Callenaere et al (2001) measured the thickness of the re-entrant jet using acoustic probes and found shedding to be dependent on the jet thickness, with thicker re-entrant jets resulting in shedding.…”
mentioning
confidence: 99%
“…For the current study the complex part of the mixture impedance is assumed to be negligible since o" w >> 2 1rfFL e,, where a." is the conductivity of water (-3.5 IuS cm), f is the input frequency (-10 kHz), FL is the non-dimensionalized permittivity of the water (-80), and e, is the permittivity of a vacuum (8.85x10-2 F m -) (George et al, 2000). The real part of the mixture impedance (i.e.…”
Section: Near-wall Void Fraction Analysismentioning
confidence: 99%